2012
DOI: 10.1021/ol3000475
|View full text |Cite
|
Sign up to set email alerts
|

How O-Substitution of Sialyl Donors Affects Their Stereoselectivity

Abstract: The profound effect of substituents at C-5 of glycosyl sialosides on their stereoselectivity is well-known although the exact nature of this effect is somewhat less understood. Presented herein is a comparative study of a range of novel sialyl donors with various O-substituents. It is demonstrated that O-substituents at C-4 and C-7 may also have a significant effect on the reactivity of sialyl donors and on the stereoselectivity of chemical sialylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 32 publications
1
24
1
Order By: Relevance
“…These observations are consistent with earlier conclusions on the influence of the side chain conformation of reactivity and selectivity derived from conformationally locked models in the glucose 16 and galactose 20 series and corroborate the suggestion that those effects are predominantly stereoelectronic rather than torsional. 16,20 It follows from these arguments that the use of atypical protecting group systems in sialyl donors, such as the recent use of silyl ethers at O4 and/or O7, 76 may influence anomeric selectivity through the modulation of side chain conformation as well as more directly through their arming or disarming nature. It also follows, however, that care must be taken in the assignment of anomeric configuration in such systems because standard empirical rules do not necessarily transpose to the new system; 41-42,73-75 the only reliable method in our opinion being the magnitude of the 3 J C,H heteronuclear coupling constant between the anomeric carboxylate carbon and the axial H3 for compounds with established chair conformations.…”
Section: Resultsmentioning
confidence: 99%
“…These observations are consistent with earlier conclusions on the influence of the side chain conformation of reactivity and selectivity derived from conformationally locked models in the glucose 16 and galactose 20 series and corroborate the suggestion that those effects are predominantly stereoelectronic rather than torsional. 16,20 It follows from these arguments that the use of atypical protecting group systems in sialyl donors, such as the recent use of silyl ethers at O4 and/or O7, 76 may influence anomeric selectivity through the modulation of side chain conformation as well as more directly through their arming or disarming nature. It also follows, however, that care must be taken in the assignment of anomeric configuration in such systems because standard empirical rules do not necessarily transpose to the new system; 41-42,73-75 the only reliable method in our opinion being the magnitude of the 3 J C,H heteronuclear coupling constant between the anomeric carboxylate carbon and the axial H3 for compounds with established chair conformations.…”
Section: Resultsmentioning
confidence: 99%
“…[10] As ar esult, for each sialyl linkage construction systematic optimizations are required in order to achieve synthetically useful efficiency. [10] Hence,the current chemical syntheses of sialosides can hardly satisfy the modern glycobiology and glycopharmacology demands,c alling on novel and efficient sialylation protocols.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Although equipped with these available strategies,t he efficient access of sialosides by chemical synthesis is still by no means at rivial problem as all strategies suffer from seriously limited generality and thus are highly substratesensitive. [10] As ar esult, for each sialyl linkage construction systematic optimizations are required in order to achieve synthetically useful efficiency. [10] Hence,the current chemical syntheses of sialosides can hardly satisfy the modern glycobiology and glycopharmacology demands,c alling on novel and efficient sialylation protocols.…”
Section: Introductionmentioning
confidence: 99%
“…[9] On the other hand, in 2012, De Meo and co-workersr eportedt hat an N-acetyl thiosialoside possessing a tert-butyldimethylsilylether at the C4 position showedap reference for a-stereoselectivity when CH 2 Cl 2 was used as the solvent. [10] In addition, Ts vetkova nd co-workersh ave reported that O-chloroacetylprotected sialyl donors exhibit improved reactivity and a-selectivity in sialylation in comparison with the O-acetyl sialyl donor. [11] These resultss uggested to us that the O-acyl protecting groups at the a-face interfere with the a-selective glycosidation by blocking the a-face of the oxoniumcation.…”
Section: Introductionmentioning
confidence: 99%
“…Glycosidation of the a-thiosialoside a-1 f provided a-sialoside 4fA in ac omparable yield and a-selectivity.T hese resultsi ndicatet hat the a-selectivity did not depend on stereochemistry of the leaving group at the anomeric position. We next examined solvent effects on the a-selective glycosidation of the sialyl donor b-1 f (entries[6][7][8][9][10]. Treatment of the donor b-1 f and the acceptor 3A with NIS andT fOH in acetonitrile at À40 8Cr esulted in the partial activation of the donor b-1 f to provide sialoside 3fA in 44 %y ield with a/b = 88:12 along with the recovered donor b-1f (39 %).…”
mentioning
confidence: 99%